El concepto de salud mental en algunos instrumentos de políticas públicas de la Organización Mundial de la Salud (2015)
ABSTRACT: To describe the historical context that gave rise to the concept of mental health official of the World Health Organization (WHO) in 1950 and examine their presence (or absence) of certain instruments in public health policies of this organization, as defined of the concept determines the policies, programs and actions in the field of mental health improvement. Methodology: desk research, historicalhermeneutic. Primary and secondary sources were consulted, as well as policy instruments of WHO selecting those that were relevant to the analysis of the concept of mental health. Results: The concept of mental health of WHO built in 1950 is still in force, with slight modifications in its formulation; derived from political and social interests, rather than scientific. On the other hand, official documents about WHO mental health considered, mostly, mental health as absence of disease, and give little room for a positive concept of mental health. Conclusions: Although the official WHO documents derive a concept of mental health, emphasize, gradually, to a focus on human rights and social determinants of health, thereby highlighting the political and social nature of mental health in accordance with the historical policies that gave rise to the concept conditions.